Effect of Vitamin A and Zink Intake of Breastfeeding Mothers on Infection in Infants (Medico Legal Update, 2019)
Background: Breastmilk is an important nutrient for newborn baby that can improve health and reduce morbidity so the babies are expected to achieve an optimal growth and development according to their abilities so that later they can become a nation’s successor with high quality and competitiveness. However, giving exclusive breastfeeding based on The “Basic Health Research” is increasingly alarming, namely the average coverage of exclusive breastfeeding in 2013, which was 67.80% and decreased by 61.0% in 2014. Ministry of Health of Republic of Indonesia in 2017 set a target of achieving 44% Exclusive Breastfeeding, but the achievement was 35.7%.Purpose: Knowing the effect of Vitamin A and Zink Intake for Breastfeeding Mothers on Infection in Infants in the Sudiang Raya Health Center.Method: This research was an survey with cross sectional design. Sample were breastfeeding mother that selected by simple random sampling. The collected data were analyzed using contingency coefficient.Result: In general breastfeeding mothers get less vitamin A and zinc. The frequency of infection was twice that of 59.79 percent. The results of the Spearman test showed p-value = 0.000, with a correlation coefficient marked negative, so it was concluded that the intake of vitamin A breastfeeding mothers correlated with the frequency of infectious diseases in infants.Conclusion: Reduced intake of vitamin A will have an impact on increasing the frequency of infections in infants.